PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA DOSEN - Muttaqiyathun, Ani (Journal of Innovation in Business and Economics, 2011)
This research aimed to analyze the effect of emotional, intellectual and spiritual quotient upon lecturer’s performance in Jogjakarta private universities. Multiple regression analysis applied in the research. The result show that the lecturer’s performance significantly affected by emotional, intellectual and spiritual quotient, both simultaneously and partial. The spiritual quotient gives more contribution influence to lecturer’s performance than emotional quotient and intellectual quotient. According on the result, emotional, intellectual and spiritual quotient  show very significantly influence to increase the lecturers performance.